The transcendentalists and their world - Gross, Robert A. 1945- (Farrar, Straus and Giroux, 2021)
"The eminent and award-winning historian Robert A. Gross presents his long-awaited, immersive journey through Concord in the age of Emerson and Thoreau"--
Includes index
Keywords: Transzendentalismus; Concord, Mass.; USA; Transcendentalism (New England); Transcendentalists (New England)